Genetic and Phenotypic Analyses of a Papaver somniferum T-DNA Insertional Mutant with Altered Alkaloid Composition - Kayo Yoshimatsu; Noriaki Kawano; Fumiyuki Kiuchi; Nobuo Kawahara (MDPI AG, 2012)
The in vitro shoot culture of a T-DNA insertional mutant of Papaver somniferum L. established by the infection of Agrobacterium rhizogenes MAFF03-01724 accumulated thebaine instead of morphine as a major opium alkaloid. To develop a non-narcotic opium poppy and to gain insight into its genetic background, we have transplanted this mutant to soil, and analyzed its alkaloid content along with the manner of inheritance of T-DNA insertion loci among its selfed progenies. In the transplanted T0 primary mutant, the opium (latex) was found to be rich in thebaine (16.3% of dried opium) by HPLC analysis. The analyses on T-DNA insertion loci by inverse PCR, adaptor-ligation PCR, and quantitative real-time PCR revealed that as many as 18 copies of T-DNAs were integrated into a poppy genome in a highly complicated manner. The number of copies of T-DNAs was decreased to seven in the selected T3 progenies, in which the average thebaine content was 2.4-fold that of the wild type plant. This may indicate that the high thebaine phenotype was increasingly stabilized as the number of T-DNA copies was decreased. In addition, by reverse transcription PCR analysis on selected morphine biosynthetic genes, the expression of codeine 6-O-demethylase was clearly shown to be diminished in the T0 in vitro shoot culture, which can be considered as one of the key factors of altered alkaloid composition.